Studies on C18-C20 aldol couplings of rhizopodin - Dieckmann, Michael; Rudolph, Sven; Lang, Carolin; Ahlbrecht, Wiebke; Menche, Dirk (Synthesis, 2013)
The aldol addition of an enol(ate) to a carbonyl compound is one of the most powerful and versatile C-C bond forming reactions. In complex target synthesis the coupling of two chiral partners may complicate the stereochemical outcome by multiple stereoinductions. Here, we report studies on pivotal aldol couplings employed in the rhizopodin synthesis, detailing the various directing effects exerted by the stereogenic centers present in this sterically hindered connection.